Ethnobotanical Assessment of Medicinal Climbers of Amroha District of Western Uttar Pradesh - Krati Tandon, Ashok Kumar, Sameer Chandra, Pashupati Nath (South Eastern European Journal of Public Health, 2025)
The present study emphasise on the climbers having medicinal values and the native of the western Uttar Pradesh region. The Ethnobotanical data has collected by interview of 100 informants which included local plant collectors, elderly villagers, and traditional healers. There are 21 families and 46 species of medicinal climbers are identified. The Cucurbitaceae, Convolvulaceae, and Fabaceae groups are the well-represented. The most often utilised plant parts were the leaves, which were followed by the roots and stems. The majority of the known medicinal climbers were used to treat urogenital issues, diabetes, lung conditions, gastrointestinal issues, skin conditions, and jaundice. In order to statistically assess the ethnobotanical data, the study also employed the utilisation value (UV), relative frequency of citation (RFC), and informant consensus factor (ICF).Ethnobotanical indices such asUV,RFC, and ICF can be analyzed quantitatively to assess the cultural significance of plants, rank species for further study or conservation priority, and provide information about local ecological knowledge and traditional resource management practices. This approach recognizes the importance of traditional knowledge while fostering a sense of community responsibility over conservation efforts. Additional formulations and research on each species can help steer the creation of innovative medications that have great promise for the future. The medicinal climbers with high RFC and UV values were Clitoria ternateaL., Convolvulus microphyllusL., Tinospora cordifolia (Thunb.) Miers, Asparagus racemosusWilld, Cucurbita maxima Duchesne. Informant consensus about uses of medicinal climbers was high for several disease categories such as Skin diseases, Digestive problems, Respiratory illness, Diabetes and Gynaecological disorders. The findings highlight the rich diversity of medicinal climbers in western Uttar Pradesh and the associated traditional knowledge.